Monte-Carlo simulation for fragment mass and kinetic energy distributions from neutron induced fission of U-235 - Montoya, Modesto (2003)
Mass and kinetic energy distribution of nuclear fragments after neutron induced fission of U-235 have been studied using a Monte-Carlo simulation. Besides that the pronounced peak in the standard deviation of the kinetic energy σE(m) at the mass number around m = 110 was reproduced, a second peak was found at m = 126. These results are in good agreement with experimental data obtained by Belhafaf et al. We have concluded that the obtained results are consequence of the characteristics of neutron evaporation for the fragments and sharp variation on primary mass yield curve.